ANALISIS KADAR VITAMIN C EKSTRAK ETANOL DAUN KELOR (Moringa Oleifera Lam) DARI DESA KAIRATU MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Jamila F. Kabakoran; Amelia Niwele; Sitti Zaenab (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2020)
Moringa leaves (Moringa oleifera lam) is a type of plant from the Moringacecae tribe. Moringa leaves are found everywhere, but in the community, Moringa leaves are only used as a fence or garden barrier, but in fact Moringa leaves are one of the plants that contain lots of nutrients, both minerals and vitamins, one of which is vitamin C. The problem of this research is that many people do not knowing that Moringa leaves contain a lot of vitamin C so it is very good for consumption, especially during the COVID-19 pandemic like today. This study is a quantitative study that aims to determine the levels of vitamin C in the ethanol extract of Moringa leaves (Moringa Oleifera Lam) in Waiselang Hamlet, Kairatu Village. The sampling technique used in this research is purposive sampling. Moringa leaves were extracted using maceration method with 70% ethanol solvent for 7 days and analyzed using UV-Vis spectrophotometry at a wavelength of 560 nm. The results obtained were calculated using a linear regression equation and showed that the vitamin C content of the ethanolic extract of Moringa leaves (Moringa Oleifera Lam) in Waiselang Hamlet, Kairatu Village on average was 85.030 mg/100gr.